PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT GENERASI Z DI MEDIASI OLEH STRES KERJA PADA RSUD DR. PIRNGADI MEDAN - Zahra, Aqilla Ulayya; Saputra, Ahmad; Julfizar (Skena Bisnis, 2026)
This study aims to analyze the effect of workload and work environment on the performance of Generation Z nurses at Dr. Pirngadi Regional General Hospital, Medan, with job stress as a mediating variable. Using a quantitative approach with path analysis on 61 respondents, data were collected through validated and reliable questionnaires. The results show that workload and work environment significantly and positively affect job stress and performance, while job stress negatively affects performance. Moreover, job stress mediates the relationship between workload, work environment, and performance. These findings suggest that balanced workload management and a supportive work environment can reduce stress and enhance nurse performance.